2017
DOI: 10.1080/14787210.2017.1305888
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of cationic amphiphilic drugs

Abstract: Emerging and reemerging viral infections represent a major concern for human and veterinary public health and there is an urgent need for the development of broad-spectrum antivirals. Areas covered: A recent strategy in antiviral research is based on the identification of molecules targeting host functions required for infection of multiple viruses. A number of FDA-approved drugs used to treat several human diseases are cationic amphiphilic drugs (CADs) that have the ability to accumulate inside cells affectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
130
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(136 citation statements)
references
References 106 publications
1
130
0
5
Order By: Relevance
“…8 Other mechanisms may include raise in endosomal pH in host cells thereby inhibiting auto-lysosome fusion and disrupting the enzymes needed for the viral replication. 9,10 Hydroxychloroquine (HCQ) is synthesized by N-hydroxyethyl side chain substitution of chloroquine. This modification renders HCQ more soluble than chloroquine which may confer advantage of relative lesser toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…8 Other mechanisms may include raise in endosomal pH in host cells thereby inhibiting auto-lysosome fusion and disrupting the enzymes needed for the viral replication. 9,10 Hydroxychloroquine (HCQ) is synthesized by N-hydroxyethyl side chain substitution of chloroquine. This modification renders HCQ more soluble than chloroquine which may confer advantage of relative lesser toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no commercial vaccines or specific therapies are available for EBOV. However, various studies have been reported that explain the comprehensive development of vaccines, small‐molecule inhibitors, and repurposed Food and Drug Administration (FDA) approved drugs against Ebola . Table provides an overview of anti‐EBOV compounds and their level of efficacy, reported in either IC 50 or EC 50 , in vitro assays against EBOV, clinical status, and observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…From Table 2, adapted from Salata 2017 [32], it can be seen that commercially available cationic amphiphilic drugs screened for their antiviral activity often exhibit antiviral activity against different types or families of viruses, with similar IC 50 /EC 50 . It is possible that a number of agents from this list could also be active against the COVID-19 virus.…”
mentioning
confidence: 99%